2017
DOI: 10.12659/msm.898221
|View full text |Cite
|
Sign up to set email alerts
|

5-Aminolaevulinic Acid-Based Photodynamic Therapy Restrains Pathological Hyperplasia of Fibroblasts

Abstract: BackgroundThis study aimed to explore whether 5-aminolaevulinic acid-based photodynamic therapy (ALA-PDT) restrains pathological hyperplasia of fibroblasts from hyperplastic scar tissues, and to investigate the potential mechanism.Material/MethodsWe used MTT assay, flow cytometry, and terminal-deoxynucleotidyl transferase mediated nick-end labeling (TUNEL) to examine the effects of ALA-PDT on proliferation, cell cycle, and apoptosis of fibroblasts isolated from hyperplastic scar tissues. The growth-promoting e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Several reports demonstrated that 5-ALA itself could cause cell damage. Wang et al showed that 1.5 mM of 5-ALA significantly inhibited cell viability of human fibroblasts [ 33 ]. Moreover, Ito et al assessed the effect of 5-ALA on normal gastric epithelial cells, which revealed that 5-ALA induced caspase 3 activation, p53 phosphorylation, and subsequent apoptosis [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several reports demonstrated that 5-ALA itself could cause cell damage. Wang et al showed that 1.5 mM of 5-ALA significantly inhibited cell viability of human fibroblasts [ 33 ]. Moreover, Ito et al assessed the effect of 5-ALA on normal gastric epithelial cells, which revealed that 5-ALA induced caspase 3 activation, p53 phosphorylation, and subsequent apoptosis [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dynamic biological changes in fibroblasts have been found to be related to the formation and progression of hypertrophic scar [4,24]. The hyper-expression of TGF-b1 and VEGF in fibroblasts both contributes to the progression of hypertrophic scar [4].…”
Section: Discussionmentioning
confidence: 99%
“…The second generation photosensitizer 5-aminolevulinic acid (ALA) is a precursor of endogenous protoporphyrin IX (PpIX), a photosensitizer. PpIX is produced in the mitochondria and is catalyzed by heme synthase in the presence of ALA (12). When the irradiation of the light source matches the absorption spectrum of the photosensitizer, the two ALA molecules are catalyzed by ALA dehydratase to form porphobilinogen and tetrapyridine porphyrin III, a common precursor of all tetrapyrrole substances.…”
Section: Introductionmentioning
confidence: 99%